INCENTIVES FOR DISHONESTY: AN EXPERIMENTAL STUDY WITH INTERNAL AUDITORS. (9th January 2020) - Balafoutas, Loukas; Czermak, Simon; Eulerich, Marc; Fornwagner, Helena
Abstract : We conduct an experiment with professional internal auditors and evaluate their performance and objectivity, measured as the extent to which they truthfully report the performance of other participants in a real‐effort task. In line with our hypotheses, we find that incentive‐based compensation increases dishonest behavior: competitive incentives lead to under‐reporting of other participants' performance, while collective incentives lead to over‐reporting of performance. We replicate these results with a student sample. In addition, we find that moving from an environment with objective performance evaluation toward a peer evaluation scheme reduces performance among internal auditors, but not among students.( JEL C93, M42, M52)